Estudi dels exempla als Avisos de sant Antoni Maria Claret. - MOLLÁ, HÈCROR SANCHIS (Scripta)
The religious literature of the nineteenth century has been recently treated by scholars. In this paper, we discuss a resource par excellence of this literature: the exemplum. In particular, we find out the source of the examples used by St. Antoni Maria Claret works: Avisos saludables a las donsellas (1850), Avisos molt útils á las viudas (1848), Avisos molt útils als pares de familia (1845) i Avisos saludables als noys (1851). Also, we indicate if the examples have been used by other contemporary authors.